Synthesis of Polycrystalline Bi-Doped Snse by Mechanical Alloying and Hydrogen Reduction - Jin Kwang Jang; Jaeyun Moon; Jongmin Byun (Archives of Metallurgy and Materials)
In this study, Bi-doped SnSe was fabricated through the high energy ball milling and the hydrogen reduction of Bi2O3, and its thermoelectric properties were analyzed. The specimen with pure-Bi was fabricated as a control group and properties were compared. In the case of specimens with added Bi2O3, when sintering was performed in a hydrogen atmosphere, Bi2O3 with a high melting point was reduced to Bi with a relatively low melting point. At this time, because of the appearance of the liquid phase, the orientation of the (400) plane increased, and the density was improved. As a result, the change of SnSe to n-type was confirmed in the temperature range of 300 K - 773 K due to Bi doping. Additionally, when Bi2O3 was used instead of pure-Bi, the thermal conductivity, which is inversely proportional to the figure of merit, decreased, and the electrical conductivity increased, resulting in an improvement in the figure of merit.